Developing access and benefit-sharing regimes Plant genetic resources for food and agriculture: Policy brief - January 2006 - International Plant Genetic Resources Institute (2006)
This brief was developed by Gerald Moore and Michael Halewood of the International Plant Genetic Resources Institute (IPGRI) with contributions from Ruaraidh Sackville-Hamilton and Mike Jackson of the International Rice Research Institute (IRRI). First published as IPGRI/IRRI. 2005. Developing access and benefit-sharing regimes: Plant genetic resources for food and agriculture. IPGRI, Rome, Italy.